Duck, R., Worship for the whole people of God. Vital worship for the 21st century - M. Laubscher (Acta Theologica)
From text: As teachers of Christian worship, we are always reflecting on and seeking whether we have the best possible resources available to welcome and guide our undergraduate students into this critical field of studying and doing theology. Well, cometh the hour, cometh the book! The majority of the scholars in the field have the greatest respect for James F. White’s influential textbook Introduction to Christian worship (Third Edition Revised and Expanded – 2000). However, what was helpful at the end of one era is not necessarily so at the beginning of the next.